PERBANDINGAN KEPEMIMPINAN NEGARA MALAYSIA DAN INDONESIA SEBAGAI NEGARA YANG MENGANUT SISTEM DEMOKRASI: - , Siti Marwah; Eka Yulyana (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Indonesia and Malaysia are two developing countries in the Asean region with similarities in adopting a democratic system for their government. A democratic system that implements the division of power into three parts according to Montesquieu's theory, namely legislative, judicial and executive. Malaysia is a federal country and Indonesia is a republic. The application of democracy is also demonstrated by delegation through general elections, in this case the community is involved in making decisions regarding who has the right to represent them and elect the head of state. The research was carried out through a qualitative literature study approach using linear references to research literatur from various scientific articles to methodically compile or obtain scientific knowledge. The results of this study found that there are various differences in leadership applications even though both adhere to a democratic system. This is motivated by various factors including, background, form of country, ideology and philosophy.